Pengendalian Kualitas Produk Komponen Foxing pada Departemen Moulding di PT. Agung Pelita Menggunakan Metode Statistical Process Control (SPC) - Septian Rahmat Adnan; Jesica Jepni D. A; Nofi Erni; Taufiqur Rachman (Jurnal Optimalisasi, 2021)
PT Agung Pelita Industrindo is a company engaged in the shoe industry that specializes in producing accessories or shoe components for various types of shoes. One of the products produced is the Foxing component product, which is a component produced for the NIKE Air Max Plus type of shoe. Based on the results of observations, it is known that the production process for Foxing component products still has product defects and The purpose of this research is to control the quality of the product of the foxing component at PT. Agung Pelita and to get information the most dominant types of defects in the Foxing production process and the factors causing the occurrence of defective products using the Statistical Process Control (SPC) method and providing suggestions for improvements to reduce the number of defective products. From the results of the analysis obtained six types of defects produced in the Foxing component production process, the more dominant type of defect is waste defects, namely defects that occur due to unwanted small prints on Foxing component materials, so that the proposed improvements that can be made by PT Agung Pelita Industrindo to reduce the number of waste defects in the production process of Foxing's component products is to hold outreach to operators to improve understanding of SOPs related to mold cleaning.